Effects of exercise interventions on sleep quality in adolescents: a systematic review and meta-analysis - Yan, Haoming; Xin, Guangjie; Chen, Rui (Frontiers in Public Health, 2025)
ObjectiveAdolescents’ declining sleep quality has caught the attention of educators, parents, doctors, and schools. Research, especially focusing on teenagers, is still lacking, despite numerous studies examining the connection between physical exercise and sleep quality across other demographics. This study aims to systematically review and conduct a meta-analysis to evaluate the impact of exercise interventions on adolescents’ sleep quality.MethodsInvestigate articles available until April 17, 2025, in databases such as PubMed, Cochrane, Web of Science, EBSCO, and Embase. Evaluate the quality of the studies based on the standards outlined in the Cochrane Handbook and conduct data analysis with Review Manager 5.3 software.ResultsAfter screening 2,312 articles, 8 studies involving 710 participants were ultimately included for meta-analysis. The meta-analysis results indicated that exercise effectively improves sleep quality in adolescents (SMD = −2.10, 95% CI: −2.86 to −1.35, p < 0.05). Various weekly exercise frequencies, single-session lengths, and total intervention durations all demonstrated statistically significant favorable impacts on adolescents’ sleep quality, according to subgroup analyses. Regarding exercise modality, combined exercise demonstrated no significant effect on adolescents’ sleep quality, whereas both aerobic and resistance exercise produced significant improvements.ConclusionExercise can effectively improve sleep quality in adolescents. A systematic exercise program lasting 3 to 12 weeks is beneficial for the sleep quality of adolescents, with the maximum benefit achieved at 12 weeks. Conducted at an appropriate frequency and with each session lasting more than 30 min, it is particularly effective in improving the sleep quality of adolescents. Both aerobic and resistance exercise significantly improve adolescents’ sleep quality, whereas combined exercise shows no significant effect. Parents and educators should see exercise treatments as a practical, secure, and efficient non-pharmacological way to improve adolescents’ sleep quality.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251033597, Identifier CRD420251033597.